Geographic distribution of corneal staining in symptomatic dry eye - Woods, Jill; Hutchings, Natalie; Srinivasan, Sruthi; Jones, Lyndon (The ocular surface, 2020)
To describe the geographic distribution of corneal fluorescein staining across the five corneal zones, among non contact lens wearers who report symptoms of dry eye and determine which corneal zone most frequently exhibited the worst staining. Prior studies conducted at the Centre for Ocular Research & Education, Canada, were reviewed for inclusion in the analysis. Each study assessed dry eye symptoms using OSDI and also assessed corneal fluorescein staining in five corneal zones. For each subject, the corneal zones were ranked 1–5 according to their relative staining grade, Rank-1 representing the highest grade. Data from 13 studies and 368 subjects were included. The total number of zones assigned Rank-1 (worst) staining was 449 (across 264 subjects). The inferior zone had the most Rank-1 counts of all zones at 193/43%, which involved 52.5% of all subjects. The nasal zone had 77/17% involving 20.9% of subjects, followed by the temporal (69/15.5%, 18.8% subjects) and superior zones (63/14%, 17.1% subjects). The central zone had the lowest count of Rank-1 designations, at only 47/10.5%, involving 12.8% of subjects. Bayesian analysis was used to generate distributions of the credible proportions of subjects likely to present with staining in a single peripheral zone, with or without central zone staining. It illustrated that staining in a peripheral zone without central staining was more credible. The worst single zone staining was most likely to present in the inferior zone (67.9%), followed by the nasal zone (11.3%), the superior zone (9.2%), and the temporal zone (5.6%). In the presence of dry eye symptoms, the inferior zone typically presents the most severe grade of corneal staining, more likely without central zone staining. This knowledge is valuable when developing a strategy to treat dry eye signs, as the inferior corneal zone has the highest grade of staining thus has the potential to exhibit the greatest reduction in staining post-treatment.